Assessing the Environmental Kuznets Curve in MENA Countries: A Dynamic Panel Analysis of the Energy Growth Environment Nexus using a Translog Functional Form - Fridhi, Bechir; Brini, Riyadh (International Journal of Energy Economics and Policy, 2025)
This study investigates the relationship between toxic gas (TG) emissions, energy consumption, and economic growth in ten Middle East and North Africa (MENA) countries from the period 1994–2024, with a particular emphasis on testing the Environmental Kuznets Curve (EKC) hypothesis. The analysis employs a panel econometric framework based on a Transcendental Logarithmic functional form, which allows for the identification of linear, non-linear, and interaction effects among the variables. To ensure methodological robustness, Fixed and Random Effects models were estimated, with the Hausman test supporting the Fixed Effects specification, while heteroscedasticity, autocorrelation, and cross-sectional dependence were addressed using the Feasible Generalized Least Squares method. Endogeneity issues were mitigated through dynamic panel techniques, notably the System- GMM estimator, and the validity of long-run equilibrium relationships was confirmed through panel unit root and cointegration tests. The results demonstrate that energy consumption has a substantially stronger positive effect on TG emissions compared to GDP per capita, highlighting fossil fuel dependency as the primary driver of environmental degradation. Moreover, the negative and significant coefficient of the quadratic GDP term validates the EKC hypothesis, suggesting that emissions decline at higher income levels. These findings underscore the urgency of accelerating renewable energy adoption, enhancing energy efficiency, and strengthening environmental governance to achieve sustainable development in the MENA region.